2021
DOI: 10.3390/su14010029
|View full text |Cite
|
Sign up to set email alerts
|

The Pedospheric Variation of DTPA-Extractable Zn, Fe, Mn, Cu and Other Physicochemical Characteristics in Major Soil Orders in Existing Land Use Systems of Punjab, India

Abstract: The agricultural production in Punjab has increased manifold that aggravated the deficiencies of micronutrients in soils and plants. The availability of soil micronutrients in different soil orders depends upon the soil mineralogy, topography, climatic conditions and cropping sequences. Hence, to study the pedospheric variations of DTPA-extractable micronutrients, viz., zinc (Zn), iron (Fe), manganese (Mn) and copper (Cu), in three prominent soil orders of Punjab, a total of 144 depth-wise soil samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The results revealed that the distribution of DTPA-Cu slightly decreased with increasing depth. The fact that organic matter in the form of crop residues has been added to the surface layer of soils, reducing pH, may be the cause of the greater Cu content on surface soils [13]. The soils under this cropping system were sufficient in available copper content.…”
Section: Dtpa Extractable Coppermentioning
confidence: 92%
See 4 more Smart Citations
“…The results revealed that the distribution of DTPA-Cu slightly decreased with increasing depth. The fact that organic matter in the form of crop residues has been added to the surface layer of soils, reducing pH, may be the cause of the greater Cu content on surface soils [13]. The soils under this cropping system were sufficient in available copper content.…”
Section: Dtpa Extractable Coppermentioning
confidence: 92%
“…Mean values of CEC 15.96, 13. 13 , DTPA Mn 8.20, 6.80 and 5.20 mg kg -1 and DTPA Cu 0.99, 0.74 and 0.56 mg kg -1 were recorded at 0-15 cm, 15-30 cm and 30-45 cm, respectively. Soils under this cropping system were low in available nitrogen content and medium in available phosphorus and potassium content.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations